2010
DOI: 10.1088/0022-3727/43/22/225403
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of hard thin films from HMDSO in atmospheric pressure dielectric barrier discharge

Abstract: To cite this version:DAbstract. The atmospheric pressure dielectric barrier discharge burning in nitrogen with small admixture of hexamethyldisiloxane (HMDSO) was used for the deposition of thin organosilicon films. The thin films were deposited on glass, silicon and polycarbonate substrates, the substrate temperature during the deposition process was elevated up to values within the range 25 • C -150 • C in order to obtain hard SiO x -like thin films. The properties of the discharge were studied by means of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 41 publications
6
53
0
Order By: Relevance
“…This may result in the less desirable Si-O-H configuration, which is a deep electron trap [18,19]. HMDSO has already been used in the literature to deposit thermally stable SiO 2 layers [20] and dielectric barrier layers [21]. It was suggested that the Si-C bonds dissociate first and that the Si-O-Si bond remains intact during HMDSO decomposition in a plasma [22].…”
Section: Methodsmentioning
confidence: 99%
“…This may result in the less desirable Si-O-H configuration, which is a deep electron trap [18,19]. HMDSO has already been used in the literature to deposit thermally stable SiO 2 layers [20] and dielectric barrier layers [21]. It was suggested that the Si-C bonds dissociate first and that the Si-O-Si bond remains intact during HMDSO decomposition in a plasma [22].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma enhanced chemical vapor deposition of silicon-organic films at atmospheric pressure (AP-PECVD) is commonly performed with a wide variety of precursors [15][16][17][18]. The most prominent class of precursors in use is alcoxysilanes (e.g.…”
Section: Surface and Coatings Technology 295 (2016) 112-118mentioning
confidence: 99%
“…A common property of DBDs is that in most gases at atmospheric pressure, breakdown is initiated in a large number of short-lived independent current filaments or microdischarges [32,35]. Because of this lack of uniformity, numerous efforts have been undertaken to homogenise DBDs and it has been found that under certain conditions homogeneous DBDs or so-called atmospheric pressure glow discharges (APGDs) can be obtained [36][37][38]. With respect to a uniform thin film deposition, a homogeneous discharge condition is very desirable, however, in practice, it is generally believed to be difficult and tricky to reliably control such homogeneous DBDs [39].…”
Section: Introductionmentioning
confidence: 99%